A systematic review of the technological factors affecting the adoption of advanced IT with specific emphasis on building information modeling - Elghdban, Mohamed Ghayth; Nurhidayah, Azmy; Adnan, Zulkiple; Al-Sharafi, Mohammed A. (Springer Nature, 2021)
Despite the sensitivity of the architecture, engineering, and construction (AEC) industry to the changes in demographic factors, economic activity, and social development, the industry is consistently progressing and becoming more successful. Organizations in the AEC industry are lagging in the adoption of advanced IT. For instance, Building Information Modelling (BIM) is among the top technologies utilized by the industry. BIM is extensively known as one of the innovations of IT to have emerged within the AEC industry. Although BIM processes require organization-wide adoption, few studies focused on the technological factors influencing BIM adoption at the organizational level in the AEC industry. Therefore, the present study aims to further enrich the literature of such studies through a systematic literature review (SLR). The main objective of this SLR is to analyze the current studies that involved the technological factors that influence organizations to adopt and use advanced IT, such as BIM. Therein, 78 up-to-date studies retrieved from two primary databases (Scopus and Web of Science) were critically analyzed in the period between 2015 and October 2019. The review identified 42 technological factors that may affect BIM adoption in the AEC industry. The outcome of this SLR will add significantly to the existing literature in IT adoption in general, and BIM adoption practically.